Monocytic myeloid‐derived suppressor cells as prognostic factor in chronic myeloid leukaemia patients treated with dasatinib. Issue 2 (8th December 2017) - Giallongo, Cesarina; Parrinello, Nunziatina L.; La Cava, Piera; Camiolo, Giuseppina; Romano, Alessandra; Scalia, Marina; Stagno, Fabio; Palumbo, Giuseppe A.; Avola, Roberto; Li Volti, Giovanni; Tibullo, Daniele; Di Raimondo, Francesco
Abstract: Myeloid suppressor cells are a heterogeneous group of myeloid cells that are increased in patients with chronic myeloid leukaemia (CML) inducing T cell tolerance. In this study, we found that therapy with tyrosine kinase inhibitors (TKI) decreased the percentage of granulocytic MDSC, but only patients treated with dasatinib showed a significant reduction in the monocytic subset (M‐MDSC). Moreover, a positive correlation was observed between number of persistent M‐MDSC and the value of major molecular response in dasatinib‐treated patients. Serum and exosomes from patients with CML induced conversion of monocytes from healthy volunteers into immunosuppressive M‐MDSC, suggesting a bidirectional crosstalk between CML cells and MDSC. Overall, we identified M‐MDSC as prognostic factors in patients treated with dasatinib. It might be of interest to understand whether MDSC may be a candidate predictive markers of relapse risk following TKI discontinuation, suggesting their potential significance as practice of precision medicine.